2014
DOI: 10.15678/aoc.2014.1105
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Vertical and Horizontal Gender Segregation in the Workplace in Poland

Abstract: The aim of this article is to analyse factors influencing the level of horizontal and vertical occupational segregation in Poland. The results of qualitative and quantitative surveys conducted among Polish employees are investigated. The data are taken from a project on employee perspectives on corporate social responsibility. Ninety individual depth interviews (IDI) with participants from 22 sectors of the economy and 1000 computer-assisted telephone interviews (CATI) on a representative sample of Polish empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…In contrast, countries that place the status of women below men tend to have lower segregation. A broader study by Kacprzak (2014) discusses vertical segregation in several aspects including age, education, marital status, number, and occupation. In contrast to Gedikli (2020) who explains the vertical component of segregation is based on differences in wages, working hours, and age categories in various occupations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, countries that place the status of women below men tend to have lower segregation. A broader study by Kacprzak (2014) discusses vertical segregation in several aspects including age, education, marital status, number, and occupation. In contrast to Gedikli (2020) who explains the vertical component of segregation is based on differences in wages, working hours, and age categories in various occupations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the long history of researching and managing gender inequality at workplaces and the significant improvements made in many countries and industries in the past decades (European Union 2017; OECD 2017), typical forms of gender inequality prevail in the under-representation or gap in employment in general, and in certain industries and jobs in particular, leading to horizontal segregation. Moreover, horizontal segregation is often combined with vertical segregation manifesting in slower career advancement of women and under-representation in top managerial positions and other decisionmaking bodies such as boards and management committees (Choudhury 2015;Dämmrich -Blossfeld 2016;Kacprzak 2014;Kim -Starks 2016;Meulders et al 2010). Moreover, a persistent gender-based wage gap has been observed that is disadvantageous to women (Card -Cardoso -Kline 2015;Kangasniemi -Kauhanen 2013;Mihaila 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Örneğin,Baron vd. (1991) Amerika' da özellikle 80'li yıllarda iş yerindeki cinsiyet ayrımcılığına etki eden faktörler arasında, cinsiyet eşitliğini desteklemeyen çıkar gruplarının, kurumun ve organizasyonun büyüklüğünün önemli olduğunu vurgulamışlardır Kacprzak (2014). ise Polonya' daki yatay ve dikey düzeydeki mesleki ayrımcılığı etkileyen faktörleri tespit etmeyi amaçladığı çalışmasında, Polonya' da faaliyet gösteren çok sayıda sektörü incelemiş ve analiz neticesinde ayrımcılığın büyük çoğunluğun kültürel değerlerden ve normlardan kaynakladığını ortaya koymuştur.…”
unclassified